Wolbachia Reduces the Transmission Potential of Dengue-Infected Aedes aegypti. - Yixin H Ye; Alison M Carrasco; Francesca D Frentiu; Stephen F Chenoweth; Nigel W Beebe; Andrew F van den Hurk; Cameron P Simmons; Scott L O'Neill; Elizabeth A McGraw (Public Library of Science (PLoS), 2015)
BACKGROUND:Dengue viruses (DENV) are the causative agents of dengue, the world's most prevalent arthropod-borne disease with around 40% of the world's population at risk of infection annually. Wolbachia pipientis, an obligate intracellular bacterium, is being developed as a biocontrol strategy against dengue because it limits replication of the virus in the mosquito. The Wolbachia strain wMel, which has been introduced into the mosquito vector, Aedes aegypti, has been shown to invade and spread to near fixation in field releases. Standard measures of Wolbachia's efficacy for blocking virus replication focus on the detection and quantification of virus in mosquito tissues. Examining the saliva provides a more accurate measure of transmission potential and can reveal the extrinsic incubation period (EIP), that is, the time it takes virus to arrive in the saliva following the consumption of DENV viremic blood. EIP is a key determinant of a mosquito's ability to transmit DENVs, as the earlier the virus appears in the saliva the more opportunities the mosquito will have to infect humans on subsequent bites. METHODOLOGY/PRINCIPAL FINDINGS:We used a non-destructive assay to repeatedly quantify DENV in saliva from wMel-infected and Wolbachia-free wild-type control mosquitoes following the consumption of a DENV-infected blood meal. We show that wMel lengthens the EIP, reduces the frequency at which the virus is expectorated and decreases the dengue copy number in mosquito saliva as compared to wild-type mosquitoes. These observations can at least be partially explained by an overall reduction in saliva produced by wMel mosquitoes. More generally, we found that the concentration of DENV in a blood meal is a determinant of the length of EIP, saliva virus titer and mosquito survival. CONCLUSIONS/SIGNIFICANCE:The saliva-based traits reported here offer more disease-relevant measures of Wolbachia's effects on the vector and the virus. The lengthening of EIP highlights another means, in addition to the reduction of infection frequencies and DENV titers in mosquitoes, by which Wolbachia should operate to reduce DENV transmission in the field.